500 30-DAY SURVIVAL AND RECOVERY AFTER HIP FRACTURE BY MOBILISATION TIMING AND DEMENTIA: A UK DATABASE STUDY. (14th June 2021) - Sheehan, K J; Goubar, A; Martin, F C; Potter, C; Jones, G D; Sackley, C; Ayis, S
Abstract: Introduction: To compare 30-day survival and recovery of prefracture ambulation between patients mobilised early (on the day of or day after surgery) and patients mobilised late (2 days of more after surgery) in England and Wales. To determine whether the presence of dementia influences the association between mobilisation timing and 30-day survival and recovery. Methods: Secondary analysis of the UK National Hip Fracture Database linked to hospitalisation records for 126, 897 patients 60 years or older who underwent surgery for nonpathological first hip fracture in England or Wales between 2014 and 2016. We used logistic regression to regress survival and ambulation recovery at 30-days with respect to mobilisation timing, overall and by dementia, with adjustment for confounding using a propensity score for mobilisation treatment with respect to confounders. Results: Overall, 99, 667 (79%) patients mobilised early. Among those who mobilised early compared to those who mobilised late, the weighted odds ratio of survival was 1.92 (95% CI 1.80–2.05), of recovering outdoor ambulation was 1.25 (95% CI 1.03–1.51), and of recovering indoor ambulation was 1.53 (95% CI 1.32–1.78) by 30 days. Early compared with late mobilisation led to a 3.8% increase in the weighted probability of survival, 22.8% increase in weighted probability of recovering outdoor ambulation and 10.0% increase in the weighted probability of recovering indoor ambulation, by 30-days. Patients with dementia were less likely to mobilise early but increases in survival and ambulation recovery were observed both for those with and without dementia. Conclusion: Early mobilisation led to increase probability of survival and recovery for patients (with and without dementia) after hip fracture. Early mobilisation should be incorporated as a measured indicator of quality internationally. Reasons for failure to mobilise early should also be captured to inform quality improvement initiatives.